The role of shock index as a predictor of multiple‐trauma patients' pathways. Issue 2 (13th January 2015) - Toccaceli, Andrea; Giampaoletti, Andrea; Dignani, Lucia; Lucertini, Carla; Petrucci, Cristina; Lancia, Loreto
ABSTRACT: Objectives: This research was conducted with the aim of investigating the accuracy of the shock index (SI) in distinguishing which multiple‐trauma patients should be admitted to an intensive care unit (ICU) after treatment in an emergency room (ER). Background: The SI is an easily obtained indicator, as it corresponds to an arithmetic ratio between the two parameters that are always measured during the first‐aid treatment of multiple‐trauma patients: heart rate (HR) and systolic blood pressure (SBP). There are many studies examining the SI in the multiple‐trauma patients as a possible predictor of the destination unit. The SI is evaluated both at the trauma scene (pre‐hospital SI‐pH) and in the emergency room (SI‐ER). Design and methods: An observational study with a retrospective approach was conducted on 158 adult patients with multiple trauma. Results: The mean SI‐pH and SI‐ER values were higher in ICU patients than in‐patients discharged or admitted to a normal ward, but the difference between these two patient groups was significant only for the SI‐ER. Analysis of the receiver operating characteristic (ROC) curves confirmed that only the SI‐ER is significant as a reliable indicator for ICU admission with a best cut‐off of 1·05. However, a threshold value of 0·75 was still able to establish the correct type of destination for multiple‐trauma patients, with a sensitivity of 57·3% and a specificity of 62·5%. Conclusions: This research showed that the SI‐pH and SI‐ER values are correlated, but only the SI‐ER has shown statistical significance in terms of distinguishing the type of destination of multiple‐trauma patient (ICU, ordinary ward or discharge) after initial treatment in the ER. Relevance to clinical practice: The results of this study suggest the possibility of using SI in multiple‐trauma patients as a triage indicator to assess the patients' care complexity and to guide the choice of proper clinical paths.